Systemic lupus erythematosus camouflaging: As refractory acne in a young girl - Bijaya Mohanty; Binod Kumar (Journal of Family Medicine and Primary Care, 2019)
Cutaneous manifestations of systemic lupus erythematosus (SLE) are important diagnostic criteria as described by the revised American College of Rheumatology and Systemic Lupus International Collaborating Clinics. Patients usually present with various lupus-specific cutaneous manifestations such as malar rash, discoid rash, photosensitivity, and alopecia. Acneiform presentation of SLE is extremely rare. Review of the literature using PubMed has found only nine other reports so far. Here, we report a case who was initially treated as acne and later diagnosed as SLE.